2018
DOI: 10.1002/2017sw001750
|View full text |Cite
|
Sign up to set email alerts
|

Cross Calibration of the GPS Constellation CXD Proton Data With GOES EPS

Abstract: Accurate proton flux measurements of the near‐Earth environment are essential to the understanding of many phenomena which have a direct impact on our lives. Currently, there is only a small set of satellites capable of performing these measurements which makes certain studies and analyses difficult. This paper details the capabilities of the Combined X‐ray Dosimeter (CXD), flown on 21 satellites of the Global Positioning System constellation, as it relates to proton measurements. We present a cross calibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…The mean difference in L value between both normalization methods is listed in Table 2 for each energy with the difference percentage and the number of linked cutoffs per energy. In agreement with the cross-correlation determined by Carver et al (2018), the difference percentage is smallest (<2%) when E > 30 MeV. For higher energies, fewer cutoff L-shells are linked due to GOES differential fluxes becoming zero for both less intense SPEs and less intense periods of SPEs.…”
Section: Validation Normalization Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…The mean difference in L value between both normalization methods is listed in Table 2 for each energy with the difference percentage and the number of linked cutoffs per energy. In agreement with the cross-correlation determined by Carver et al (2018), the difference percentage is smallest (<2%) when E > 30 MeV. For higher energies, fewer cutoff L-shells are linked due to GOES differential fluxes becoming zero for both less intense SPEs and less intense periods of SPEs.…”
Section: Validation Normalization Methodssupporting
confidence: 85%
“…The first GPS spacecraft with a CXD instrument was launched in 2001 and nowadays 24 GPS satellites carry a CXD detector. To enable scientific use of the CXD detectors, Carver et al (2018) cross-calibrated the CXD proton channels with those from the Energetic Particle Sensor (EPS) onboard GOES and found that integral proton fluxes for energies >30 MeV are on average within 20% of each other. In addition, Chen et al (2020) and Carver et al (2020) have shown that CXD data can be used to reliably determine cutoff L-shells of solar energetic protons during SPEs by normalizing the proton flux with the average flux in the open field line (L > 10) region measured by CXD instruments at each moment.…”
mentioning
confidence: 99%
“… 2018 ; Carver et al. 2018 ), we provide the sensor response functions so that end users can experiment with other calibration methods, should they so choose.…”
Section: Data Calibrationmentioning
confidence: 99%
“…We use data from 20 satellites (ns53-ns59 and ns61-ns73) carrying the CXD detectors (for details, see Carver et al, 2018). It is of note that the data from ns60 were not used due to the intermittent quality issues.…”
Section: Gps Electron Flux Datamentioning
confidence: 99%